BIG DATA AS PREVENTION AND ERADICATION OF CRIMINAL ACTS ON HUMAN TRAFFICKING BASED ON INTERNET OF THINGS (IOT) AT DIRECTORATE GENERAL OF IMMIGRATION - Muhamad Iskandar Wijaya (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Human trafficking Crimes is an action against the law of the perpetrators organized for the purpose of exploitation or result of exploited persons. The number of victims of the Criminal Trade Force case occurred, requiring the government to use modern ways and techniques to prevent, arrest and eradicate the perpetrators and victims of the Human Trafficking Criminal Act. The implementation of the Internet Of Things (IoT)-based Big Data in the government sector is an appropriate step by building a data center and integrated applications between the system cores with complex data exchanges to be utilized by the Ministry, The agency or stakeholders responsible for the prevention, arrest and Eradication of human Trafficking crimes. The mode of the perpetrators who have many variations so that the government needs a complex system implementation, with the application Of Big Data based on the Internet Of Things (IoT) is believed to be able to be a reliable system for prevention, arrest and eradication of human trafficking criminal cases . Each mode is recorded in the main database so that it can be used as an analytical material to conduct supervision, control and policy determinants to realize Clean and Good Government for government agencies, especially in Directorate General of Immigration